Quantification and characterization of airborne microplastics and their possible hazards: a case study from an urban sprawl in eastern India - Mandal, Mamun; Roy, Anamika; Singh, Pardeep; Sarkar, Abhijit (Frontiers in Environmental Chemistry, 2024)
One significant way that microplastics (MPs) are transported from the air into soil and water is through deposition. Nevertheless, little is known about the contributing causes and the geographical distribution of MPs in urban air deposition. The present study determined the spatial distribution of MPs and their potential ecological risk in Malda City, West Bengal, India (from December 2023 to February 2024). The average deposition fluxes of MPs were ranging from 122.25 ± 76.96 to 387 ± 89.23 n m−2 d−1. Most of the MPs were found in small-sized (50–100 µm) with transparent (35.51%) and white (33.19%) in color. The dominant chemical compositions, such as PE (∼32%), PVC (∼24%), and PET (∼20%), and in the case of shapes such as fragments (∼38%) and films (∼29%) were the dominant types of MPs found. The geographic heterogeneity seen in the MPs distribution under investigation was mostly caused by human activity and the regions’ commercial nature. The MPs deposition fluxes are also affected by rainfall and wind speed. MPs in the deposition may provide a greater ecological concern, according to the early evaluation. According to this study, human activity has a major influence on the source and dispersion of atmospheric MPs that are deposited in urban areas.